Short-Form Video Consumption among College Students: Perceived Academic Impact and Pedagogical Potential - Ayo, Eliza B.; Tamayo, Josan D.; Tegio, Rexter G.; Sakay, Lani E. (Future Science / FSH-PH Publications, 2025)
The pervasive adoption of short-form video (SFV) platforms, including TikTok, YouTube Shorts, and Instagram Reels, among college students has sparked considerable debate regarding their influence on academic performance. This study aimed to investigate the perceived relationship between SFV consumption (considering platforms, content types, and usage patterns) and academic performance among college students, while also exploring the platforms' potential for learning enhancement. A correlational quantitative design was employed, administering an online survey to 92 college students, primarily from a single university in Manila. Data were analyzed using descriptive and correlational statistics. The study found that general short-form video (SFV) consumption during academic periods had no significant negative effect on academic performance (M = 2.18, SD = 0.86, p > 0.05). However, educational SFV content showed a strong positive influence on learning outcomes (M = 3.34, Cohen’s d = 0.82, p < 0.001), demonstrating significant benefits for academic performance. This study highlights how short-form videos (SFVs) can serve as a valuable teaching tool, aligning with the United Nations Sustainable Development Goal (SDG) 4 and 10 on Quality Education and Reducing Inequalities. It provides evidence-based strategies for using these digital platforms to develop 21st-century skills. The findings also back innovative pedagogical approaches that prepare students for digital citizenship and lifelong learning. By making educational content more accessible, SFVs can help reduce educational inequalities and contribute to SDG 10 on social inclusion.